“Young Brown Men Being Brutish”: How Police Ten 7 Portrays Māori and Pacifica People as Violent and Criminal in Aotearoa New Zealand. - Antje Deckert; Wairua Taru Grant Pukeiti; Juan Tauri (Journal of Global Indigeneity)
In 2021, the New Zealand reality-TV show Police Ten 7 was publicly criticized for feeding racial stereotypes by showing “young brown men being brutish”. While several overseas studies verify that reality-TV crime shows tend to portray non-white minorities as intrinsically criminal, such research is scarce in New Zealand. Our study sought to determine whether Police Ten 7 represents Māori and Pasifika (i.e., “brown”) people fairly in light of official police statistics; and, particularly, if any distorted representation suggests that Māori and Pasifika people are more violent. We analysed 12 episodes of Police Ten 7, aired in late 2020, quantitatively and compared our data with official police statistics. We found that, on Police Ten 7, Māori and Pasifika people are underrepresented as police officers and overrepresented as suspects, and overrepresented in violent offence categories. Also, most of the TV airtime dedicated to suspects is spent on Māori and Pasifika. We argue that these distortions are intensified through contrasting juxtapositions with white suspects who are underrepresented both as suspects and violent offenders, and overrepresented as harmless drunks and bad drivers. We conclude that together these distortions and contrasting juxtapositions serve to promote the image of Māori and Pasifika as the violent criminal other.